MEDIASI PERKARA PERSELISIHAN DALAM RUMAH TANGGA PADA PERADILAN ADAT ACEH (Studi Kasus di Kota Sabang) - Irwandi Irwandi (AL-ILMU, 2021)
Traditional institutions in the Acehnese community function as a vehicle for community participation in the administration of government, development, and society. This shows that the traditional institutions of Aceh play a role as executive, legislative and judicial. Based on the above background, the problem in this research is to find out how the mediation process is, how effective the mediation is, what are the supporting and inhibiting factors of the mediation process at the Customary Court in Sabang City. The method used in this research is the Juridical Empirical approach and data collection is used through interviews, observations and literature studies. The result of this study is that the role of customary institutions in society has its own pattern and approach, which has been recognized by the Government of the Republic of Indonesia, as an alternative for resolving disputes/conflicts in the community. Studies related to customary institutions have so far discussed the existence of traditional institutions in contemporary times and their position as mediators in resolving conflicts and also as supporters of the implementation of Islamic law. Aceh Qanun No. 9 of 2008 concerning the Guidance of Customary Life and Customs Conflicts related to marriage, domestic violence, inheritance and land ownership can be resolved by customary institutions if there are parties who report, either one of the conflicting parties or both parties who conflicted. The procedure for reporting cases of conflicts/disputes that occur in the community is by reporting to Ule Jurong and some directly to Keuchik. The place for reporting to the Keuchik is not determined because the Acehnese consider the Keuchik not only a formal leader but also an informal leader. So that most cases of conflict disputes that occur in the community are often reported directly to the Keuchik's house instead of the Keuchik's office. and regarding the supporting and inhibiting factors, namely internal and external factors.